The role of blogging in a changing society: Theory, practice, and implications - Nisiforou, Efi; Eteokleous, Nikleia (My University, 2015)
Educational blogs have remained a noteworthy component, even in an age of rapid technological development. The chapter makes an in-depth description of the blogging phenomenon as it tackles the most important findings of the international literature. It provides insights into the connection between teacher identity, within the context of higher education, by incorporating aspects of theory and practice. The practical tone reports on three case studies on the use of blogs in education. A set of evaluation criteria on blogging for educational purposes and a theoretical framework for utilizing blogging as a problem solving approach are addressed. Moreover, it stresses necessity for the development of a pedagogical framework that will guide blog integration as a learning-cognitive tool in achieving specific learning outcomes. The results underscore the importance of essential training for the effective implementation of educational blogging in teaching and learning environments. A compendium of terms, definitions and explanations of concepts are clearly explained.
Keywords: Educational blogs; Evaluation